2012
DOI: 10.1167/iovs.11-7340
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Three Blood Derivatives on Human Corneal Epithelial Cells

Abstract: PRGF promotes biological processes required for corneal epithelialization, such as proliferation and differentiation. Since PRGF effects are similar to those associated with routinely used blood derivatives, the present findings warrant further research on PRGF as a novel alternative treatment for ocular surface diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 53 publications
3
41
0
2
Order By: Relevance
“…A growing body of studies has demonstrated that EGF can accelerate reepithelialization by increasing the proliferation and cell migration of keratinocytes in acute wound [2327]. V. Frelrd et al [20] demonstrated the effect of EGF on fibroblasts proliferation, and our results confirmed the former result. In our study, EGF promoted the proliferation of fibroblasts.…”
Section: Discussionsupporting
confidence: 88%
“…A growing body of studies has demonstrated that EGF can accelerate reepithelialization by increasing the proliferation and cell migration of keratinocytes in acute wound [2327]. V. Frelrd et al [20] demonstrated the effect of EGF on fibroblasts proliferation, and our results confirmed the former result. In our study, EGF promoted the proliferation of fibroblasts.…”
Section: Discussionsupporting
confidence: 88%
“…Platelet-derived products have shown an important role in the treatment of dry eye syndrome, dormant ulcers (epithelial defects of the cornea that fail to heal), ocular surface syndrome after Laser In Situ Keratomileusis (LASIK), and for surface reconstruction after corneal perforation associated also with amniotic membrane transplantation [61,[112][113][114][115]. Furthermore, platelet derivatives appear to show therapeutic effects in some diseases such as diabetic keratitis, keratocongiuntivite sicca, traumatic post-infectious and vernal ulcers that lead to a condition known as persistent epithelial defects [116].…”
Section: Ophthalmologymentioning
confidence: 99%
“…This secretion is intense in the first hour and platelets continue synthesizing more cytokines and growth factors from their mRNA reserves for at least another 7 days [1]. More than 800 different proteins are secreted into the surrounding media [1,2], having a paracrine effect on different cell types: myocytes [3], tendon cells [3-7], mesenchymal stem cells from different origins [8-11], chondrocytes [12-14], osteoblasts [3,15,16], fibroblasts [17-19] and endothelial cells [20]. Cell proliferation, angiogenesis and cell migration are stimulated, resulting in tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%